Comfort-based performance assessment methodology for low energy residential buildings in Australia. (January 2017) - Daniel, Lyrian; Williamson, Terence; Soebarto, Veronica
Abstract: In Australia, the primary method of demonstrating compliance with the mandatory dwelling Energy Efficiency requirements of the National Construction Code (NCC), NatHERS, has been criticised as being unsuitable for assessing low energy houses that are intended to use little or no heating and/or cooling in operation. In 2013–2014, a longitudinal thermal comfort study was conducted in 40 low energy houses in Australia: 20 houses located in a cool temperate climate (Melbourne) and 20 houses located in a hot humid climate (Darwin). The households completed over 6000 thermal comfort vote surveys which were paired with corresponding environmental data collected within the dwellings. Based on this collected data a model describing the thermal preference of these two cohorts was developed. This paper offers an alternative process by which to judge the potential thermal performance of such low energy houses, using the developed comfort criteria as a performance indicator. This alternative approach is aimed at reducing energy use by demonstrating that an acceptable level of comfort can be achieved without the use of heating and/or cooling appliances. The proposed assessment methodology is aimed at providing a more appropriate pathway to NCC Energy Efficiency compliance certification for these types of low energy houses. Highlights: A thermal performance assessment method for low energy dwellings is proposed. The proposed method uses comfort criteria as a performance indicator. It is shown to be more appropriate for low energy houses than existing approaches.